Analysis of Factors that Influence the Use of Electronic Money in Indonesia - Puspa Nada Aliyah Akbar; Rima Rachmawati (International Journal of Science and Society, 2023)
This empirical study scrutinizes the factors influencing electronic money usage in Indonesia, focusing on financial literacy, security, user accessibility, and government support. Employing a quantitative approach with a descriptive and verificative analysis of data from 210 potential users, the research identifies financial literacy as a cornerstone for adoption, yet finds it insufficiently developed. Security concerns are highlighted as significant, with perceived vulnerabilities in e-money systems. Accessibility challenges, due to infrastructural and educational gaps, further impede e-money's widespread use. The government's role is deemed crucial but not yet fully effective in creating a supportive ecosystem for e-money. Despite the positive influence of these factors, the research concludes that the full potential of e-money is unrealized, with the study's limitations acknowledging unexplored variables that may also affect e-money's utilization in Indonesia. These insights aim to inform strategies to address these barriers and enhance e-money adoption in the Indonesian market.